Did the UK policy response to Covid-19 protect household incomes? - Mike Brewer; Iva Valentinova Tasseva (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2020)
We analyse the UK policy response to Covid-19 and its impact on household incomes in the UK in April and May 2020, using microsimulation methods. We estimate that households will lose a substantial share of their net income (7% on average). As a proportion of income, the losses due to the crisis are largest for previously higher-income families. However, the overall impact of the crisis on income inequality is small. Earnings subsidies (the Coronavirus Job Retention Scheme) will protect household finances and provide the main insurance mechanism during the crisis. Besides subsidies, Covid-related increases to state benefits, as well as the automatic stabilisers in the tax and benefit system, will play an important role in mitigating the income losses. Analysing the impact of a near-decade of austerity on the UK safety net, we find that, compared to 2011 policies, the 2020 pre-Covid tax-benefit policies would have been less effective in insuring incomes against the shocks. The extra benefit spending in response to the pandemic will strengthen the safety net, providing important additional income protection.
Keywords: 330; Labour Market; Households; Income Dynamics; Microsimulation; Health; Covid-19; Taxation; Welfare Benefits; Economics; Public Policy; Wages And Earnings; Unemployment